Menarche, Menstruation, Menopause and Mental Health (4M): a consortium facilitating interdisciplinary research at the intersection of menstrual and mental health - Sharp, Gemma C.; De Giorgio, Luana (Frontiers in Global Women's Health, 2023)
Menstrual and mental health form a close relationship that is under-appreciated in scientific research, clinical practice and social policy. This association is extremely complex, involving interactions between biology, psychology and social, political and structural influences on health and wellbeing. Research in these areas has traditionally been siloed: focusing on menstrual or mental health in isolation, or the interrelation from a limited one-dimensional perspective. We recognised the need for a more holistic and comprehensive approach that considers the complex interweaving nature of menstrual and mental health. In 2021, we established the Menarche, Menstruation, Menopause and Mental Health (4M) consortium as a tool to address this gap and to facilitate interdisciplinary research. This paper provides a comprehensive source of information about 4M for researchers and stakeholders who may be interested in joining or working with the consortium.